1987
DOI: 10.1088/0741-3335/29/10b/004
|View full text |Cite
|
Sign up to set email alerts
|

Whistler excitation by transformation of lower oblique resonance waves on density perturbations in the vicinity of a VLF antenna

Abstract: We study an antenna system consisting of a current loop exciting resonance cones and of an electric dipole generating ion sound waves. The transformation of lower oblique resonance waves on quasineutral density perturbations in the near field of an antenna gives rise to whistler waves on combination frequencies. Their amplitude may exceed several times the amplitude of linear whistler waves excited by the loop itself. The system may be regarded as a parametric antenna for enhanced excitation of whistlers in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…One way to increase the portion of the radiated power that goes into the whistler mode was suggested by Golubyatnikov et al [1988], who showed that increasing the plasma density in the vicinity of the antenna by several times resulted in an increase by an order of magnitude of the radiated power going into the electromagnetic part of the spectrum. Another way of increasing the radiated power that goes into the whistler mode was investigated by Fiala et al [ 1987]. If the ring antenna that operates at a frequency 001 -10 kHz and a low-frequency electric dipole antenna operating at the frequency 0)2 -1 kHz are simultaneously switched on, then an excitation of the electromagnetic part of the spectrum (see equation (61)) at the combined frequency tOl + to2 can take place because of the parametric interaction of oscillations excited at these frequencies.…”
Section: Radiated Power Of Vlf Antennamentioning
confidence: 99%
“…One way to increase the portion of the radiated power that goes into the whistler mode was suggested by Golubyatnikov et al [1988], who showed that increasing the plasma density in the vicinity of the antenna by several times resulted in an increase by an order of magnitude of the radiated power going into the electromagnetic part of the spectrum. Another way of increasing the radiated power that goes into the whistler mode was investigated by Fiala et al [ 1987]. If the ring antenna that operates at a frequency 001 -10 kHz and a low-frequency electric dipole antenna operating at the frequency 0)2 -1 kHz are simultaneously switched on, then an excitation of the electromagnetic part of the spectrum (see equation (61)) at the combined frequency tOl + to2 can take place because of the parametric interaction of oscillations excited at these frequencies.…”
Section: Radiated Power Of Vlf Antennamentioning
confidence: 99%
“…In a plasma with dissipation, the singularities become finite within the angle θ c in a spatially localized resonance cone. As noted in previous work, much of the source power due to a VLF antenna is radiated as electrostatic Lower Oblique Resonance (LOR) modes [also referred to as quasi-electrostatic whistler waves] which decay as R −1 (R is the distance from the antenna) away from the source antenna, whereas the EM whistler wave decays as [9]. Considerable experimental work has shown that the loop antennas driven within the frequency range ω LH < ω ≪ ω ce form LOR waves as expected [13].…”
mentioning
confidence: 99%
“…The group velocity (and hence the energy) of the EM whistler travels in a cone with a peak angle of 19.5 o w.r.t. Earth's magnetic field, which is known as the shadow boundary and is determined by the long wavelength inflection point in the dispersion relation [9]. Therefore, as whistler waves propagate great distances along Earth's magnetic field, they carry with it energy that pitch angle scatter highly energetic particles, causing these particles to violate the frozen in condition.…”
mentioning
confidence: 99%
See 2 more Smart Citations